Evaluasi Kinerja Campuran Beraspal dengan Bitumen Hasil Ekstraksi Penuh dari Asbuton - Suaryana, Nyoman; Susanto, Iwan; Ronny, Yohannes; Sembayang, Ida Rumkita (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Asbuton is a natural rock asphalt that can be found on the island of Buton in Southeast Sulawesi province, has a large deposits but not yet well utilized. This research aims to find out the performance of asphalt mixtures AC-WC (Asphaltic Concrete Wearing Course) and HRS-WC (Hot Rolled Sheet Wearing Course) using bitumen results from full extraction of asbuton. The research was done by experimental methods through laboratory tests then its performance was compared to convensional mixtures using asphalt oil with penetration grade of 60. The results obtained showed that the bitumen of asbuton did not meet the specification of bitumen based on penetration grade. Characteristics of hot mixture asphalt using bitumen of asbuton showed better performance in terms of the Marshall stability namely 1871 kg higher than the convensional hotmixture of asphalt, with 1100 kg for AC-WC and 1241.9 kg compared with 1094 kg for HRS-WC. In addition, the results of deformation resistance tests showed asphalt mix with pure asbuton  more resistant to rutting shown by higher dynamic stability value namely 4200 track/mm compared with 492 track/mm for AC-WC and 2739 track/mm compared with 325 track/mm. The modulus resilient value of mix with pure asbuton is also higher at temperature of 25°C and relatively the sameat temperatures of 35°C and 45°C. While the resistance of  fatigue for AC-WC and HRS-WC on the test tensile strain of 150 µs were relatively the same as hotmix asphalt using asphalt oil penetration grade of 60, but on test of  a larger tensile strain has worse fatigue resistance, especially for AC-WC.